Spatial econometric analysis of the regional commuting - Сегіда, К.; Костріков, С. (Київський національний університет імені Тараса Шевченка, 2016)
Paper authors introduce the transitional research approach – the spatial econometric analysis (SEA) – upon commuting study within a regional workforce market. The authors emphasize that both the labor migration and the commuting are two dominant issues upon studying of any workforce market either at its national level, or at the regional one. In authors’ opinion, if we attempt to understand the lower, regional migration level, we have to choose just commuting as its dominant trend. SEA has been introduced as a subject field related to both Human Geography and Regional Studies, it also involves the applied GIS-science instruments as the mandatory research tools. The relationship between the usual labor migration and commuting has been shortly examined on the theoretical level only. This research has been provided with the use of geographical information system (GIS) software for spatial modeling, analysis and visualization. Several levels of the regional commuting geodatabase update with both empirical and derivative data have been described, and its relevant mathematical content introduced. Authors’ empirical / analytical GIS-model of regional commuting has become a key component of SEA completed consequently for two scale levels: for a single administrative district (“rajon”) => for whole Kharkiv administrative oblast – a region. Different visuals represent in details all commuting trends and peculiarities within Kharkiv region borders. Authors’ theoretical / empirical model has estimated an approximated number of regular daily-weekly commuters to Kharkiv-city from the region around one hundred and thirty thousand in the period of 2012-2014. The paper conclusion outlines that further commuting research needs to extend authors’ model presented with much broader number of cross-regional commuting factors. First of all, those commuting determinants caused by the war going on the East – the area neighboring to our region – must be taken into account in one way, or in another.

При розгляді прикладу формалізованого вивчення такого суспільно-географічного феномену, як маятникова трудова міграція, авторами статті був запропонований транзитивний дослідницькій підхід – просторовий економетричний аналіз (ПЕА), який відноситься до предметних галузей суспільної географії і регіональної економіки, застосовуючи елементи прикладної геоінформатики. Впроваджувалося просторове моделювання, аналіз і візуалізація результатів через програмне забезпечення геоінформаційної системи (ГІС). Описані декілька рівнів оновлення база геоданих маятникової трудової міграції. Авторська емпірико-теоретична модель відіграла роль ключової складової ПЕА. Просторовий економетричний аналіз послідовно впроваджувався на двох рівнях масштабування: для окремого адміністративного району та по усій Харківській області.
Просторовий економетричний аналіз маятникової трудової міграції на регіональному рівні
Balakiryeva O.M., Shestakovs’kyy O. (2012) Masshtaby trudovoyi mihratsiyi ukrayintsiv: dosvid kil’kisnoyi otsinky [The scale of Ukrainian labor migration: Experience quantitative assessment], Visnyk Kharkivs’koho natsional’noho universytetu imeni V. N. Karazina, no.993 [in Ukrainian] Borisov V.A. (2001) Demografiya Uchebnik dlya VUZov. [ Demography. Textbook for High Schools], 2 publishing, Moscow: ID NOTABENE [in Russian] Holovne upravlinnya statystyky u Kharkivs’kiy oblasti (2016) [Department of Statistics in the Kharkov region,], Available at: http://kh.ukrstat.gov.ua [in Ukrainian] Mista ta rayony Kharkivs’koyi oblasti v 2014 rotsi (2014) [Cities and villages of the Kharkiv region in 2014], Kostrikov S.V. (ed.) Heoinformatsiyne modelyuvannya pryrodno-antropohennoho dovkil-lya. Naukova monohrafiya, Kharkiv, Vyd-vo KhNU. [in Ukrainian] Kupets’ O. Statystychnyy analiz mayatnykovoyi trudovoyi mihratsiyi v Ukrayini (2012) [Statistical analysis of circular labor migration in Ukraine], Formuvannya rynkovoyi ekonomiky : zb. nauk. prats’, DVNZ Kyyivs’kyy nats. ekon. un-t im. Vadyma Het’mana; special issue: Pratsya v KhKhI stolitti: novitni tendentsiyi, sotsial’nyy vymir, innovatsiynyy rozvytok: (in 2 vol.), Vol. 1. [in Ukrainian] Lihoded V. (1980) Rol’ mayatnikovoj migracii vo vzaimosvyazi gorodskogo i sel’skogo naseleniya i osnovnye zadachi ee regulirovaniya [The role of circular migration in the relationship of the urban and rural population, and the main tasks of its regulation], Problemy rasseleniya v SSSR, Moscow, Finansy i statistika. [in Russian] Lyuds’kyy rozvytok v Ukrayini: minimizatsiya sotsial’nykh ryzykiv (kolektyvna monohrafiya) [Human development in Ukraine, minimizing social risks (collective monograph)] M.Libanova (ed.), Kyiv, In-t demohrafiyi ta sotsial’nykh doslidzhen’ im. M.V.Ptukhy NAN Ukrayiny, Derzhkomstat Ukrayiny, 2010 [in Ukrainian] Mihajlova T. (1981) Osobennosti mayatnikovoj migracii v zonah vliyaniya bol’shih gorodov USSR [Features of commuting in areas of influence of the big cities of the USSR], Mayatnikovaya migraciya sel’skogo naseleniya, Moscow, Finansy i statistika. [in Russian] Nyemets’ K., Kravchenko K., Sehida K. (2016) Zmina roli mist Kharkivs’koyi oblasti – retrospektyvnyy analiz [The changing role of cities Kharkiv region – retrospective analysis], Visnyk KhNU. Seriya Heolohiya-Heohrafiya-Ekolohiya, Issue 44 [in Ukrainian] Prybytkova I. (2004) Obshchaya teoryya trudovoy mayatnykovoy myhratsyy naselenyya [The general theory of employment pendulum migration], Problemy rozvytku sotsiolohichnoyi teoriyi. Sotsia-l’ni protsesy v Ukrayini, Issue 4, Kyiv, IS NANU. [in Russian] Prybytkova I. (2011) Zminy v poselens’kiy strukturi naselennya Ukrayiny ta tendentsiyi mihratsiyi [Changes in the structure of the settlement of Ukraine’s population and migration trends], Ukrayins’ke suspil’stvo. Dvadtsyat’ rokiv nezalezhnosti. Sotsiolohichnyy monitorynh: in 2 volumes, vol.1, Kyiv, IS NANU. [in Ukrainian] Prybytkova I. (2009) Khronyky myhratsyonnykh sobytyy v Ukrayne do y posle rospada SSSR [Chronicles of migration events in Ukraine before and after the collapse of the USSR], Sotsyolohyya: teoryya, metody, marke-tynh, no.1 [in Russian] Rachkov Ye. (2011) Vplyv mihratsiynykh protsesiv na zminy chysel’nosti naselennya Kharkivs’koyi oblasti u druhiy polovyni KhKh – na pochatku KhKhI st. (za danymy zah. perepysiv naselennya 1959 – 2001 rr.) [The impact of migration on population change Kharkiv region in the second half of the XX – XXI century. (According to the Society. Census 1959 – 2001)], Aktual’ni problemy vsesvitn’oyi ta vitchyznyanoyi istoriyi : zb. nauk. pr. / nats. un-t im. V. N. Karazina, Kharkiv, Issue 14 [in Ukrainian] Rohozhyn O. (2004) Demohrafichni perspektyvy ukrayins’koho sela: istorychni peredumovy, rehional’nyy analiz i modelyuvannya [Demographic prospects Ukrainian village: the historical background, regional analysis and modeling],Kyiv, In-t problem nats. bezpeky. Shitova Yu, Shitov Yu. (2008) Mikroanaliz mayatnikovoj trudovoj migracii v Moskovskoj oblasti [Microanalysis pendulum labor migration in the Moscow region], Region: ehkono-mika i socіologіya. No.4 [in Russian] Shitova Yu, Shitov Yu. (2015) GIS-monitoring mayatnikovoj trudovoj migracii kak zadacha regional’nogo upravleniya [GIS monitoring pendulum labor migration as a problem of regional governance],Available at: http://sovman.ru/article/6206 [in Russian] Yakobinchuk V. (2009) Vplyv trudovoyi mihratsiyi na sil’s’ke bezrobittya na Kyyivshchyni [The impact of migration on the rural unemployment rate in Kyiv region], Ukrayina: aspekty pratsi, 6 [in Ukrainian] Allen T.,Arkolakis C. Trade and the Topography of the Spatial Economy / T. Allen, C. Arkolakis / Quarterly Journal of Economics. – 2014. – Vol. 129. – Vol. 3 [in English] Ali K., Olfert M.R., Partridge M.D. Urban footprints in rural Canada: Employment spillover by city size / K. Ali, M.R. Olfert, M.D. Partridge // Regional Studies. – 2011. – Vol. 45. – No. 2. [in English] Chiles J.P., Delfiner P. Geostatistics: Modeling Spatial Uncertainty. 2nd Edition / J.P. Chiles, P. Delfiner. – London – NY: Wiley, 2012. [in English] Deding M, Filges T., Omerren J.V. Spatial mobility and commuting: the case of two-earner households / M. Deding, T. Filges, J.V. Omerren // Journal of Regional Science – 2009 – Vol. –No. 1 [in English] Fujita M., Krugman P., Venables A. The Spatial Economy: Cities, Regions, and International Trade / M. Fujita, P. Krugman, A. Venables. – Cambridge, Massachussettes: The MIT Press, 2001. [in English] Henley A. Residential Mobility, Housing Equity and the Labour Market / A. Henley // Economic Journal. – 1998. – Vol. 108. [in English] Hincks S., Wong C. The Spatial Interaction of Housing and Labour Markets: Commuting Flow Analysis of North West England / S. Hincks, C. Wong // Urban Studies. – 2010. – Vol. 47. – No. 3. [in English] Huffman W.E., Feridhanusetyawan T. Migration, fixed costs, and location-specific amenities: A hazard analysis for a panel of males / W.E. Huffman, T. Feridhanusetyawan // American Journal of Agricultural Economics. – 2007. – Vol. 89. – No. 2. [in English] Kostrikov S., Sekida K. Human geography with geographical information systems / S. Kostrikov, K. Segida // Часопис соціально-економічної географії – 2013. – Vol. 15. – No. 2. [in English] Moretti E. Local Labor Markets / E. Moretti // Handbook of Labor Economics,- (ed.) D. Card, Ashenfelter, Vol. 4b, Amsterdam: Elsevier North Holland, 2011. [in English] Partridge M.D., Ali K., Olfert M.R.. Rural-to-urban commuting: Three degrees of integration / M.D. Partridge, M.K. Ali, M.R. Olfert // Growth and Change. – 2010. – Vol. 41. – No. 2. [in English] Renkow M., Hoover D. Commuting, migration, and rural-urban population dynamics / M. Renkow, D. Hoover // Journal of Regional Science – 2000 – Vol. –No. 2 [in English] Rouwendal J. Search theory and commuting behavior /J. Rouwendal // Growth and Change. – 2004. – Vol. 35. – No. 3. [in English] Shuai X. Does Commuting Lead to Migration / X. Shuai // Journal of Regional Analysis and Policy. – 2012 – Vol. 42.- No. 3. [in English] Wong C, Baker M, Webb B, Hincks S, Schulze-Baing A. Mapping policies and programmes: The use of GIS to communicate spatial relationships in England / C. Wong, M. Baker, B. Webb, S. Hincks, A. Schulze-Baing // Environment and Planning B: Planning & Design. – 2015. – Vol. 42, No.. 6. P. 1020-1039. [in English] Zax J. When is a move a Migration? / J. Zax // Regional Science and Urban Economics – 1994. – Vol. 24. [in English]
Keywords: маятникова трудова міграція на регіональному рівні; просторовий економетричний аналіз; база геоданих; геоінформаційна система; просторова змінна; ГІС-карта просторової класифікації маятникової міграції; агломерація Харкова; regional commuting; spatial econometric analysis; geodatabase; geoinformation system; spatial variable; spatially classified GISmap of commuting; Kharkiv agglomeration